Fabrication of highly transparent Y2O3 ceramics with CaO as sintering aid - Yin, Danlei (2021)
Highly transparent Y2O3 ceramics were successfully fabricated with CaO as sintering aid. The microstructure evolution, optical transmittance, hardness and thermal conductivity of the Y2O3 ceramics were investigated. It was found that doping a small amount (0.01-0.15 wt.%) of CaO could greatly improve the densification rate of Y2O3. With an optimized CaO dosage of 0.02 wt.% combined with the low temperature vacuum sintering plus hot isostatic pressing (HIP-ing), Y2O3 ceramics with in-line transmittance of 84.87% at 1200 nm and 81.4% at 600 nm were obtained.